Step-Down Antibiotic Therapy of Community-Acquired Pneumonia in Children with Burdened Allergologic History and Concomitant Allergic Pathology: Focus on Cefpodoxime Proxetil - Yu.V. Marushko; G.G. Shef; O.S. Movchan (Zaslavsky O.Yu., 2013)
The use of cefpodoxime proxetil in children with community-acquired pneumonia is effective. In patients with burdened history of allergic events and concomitant allergic pathology, use of cefpodoxime proxetil does not cause allergic reactions or worsening of comorbid allergic disease and does not affect the level of total serum immunoglobulin E, indicating safety of the drug usage in such children.